Microbiological analysis of domestic water sources in Banda slum of Kampala, Uganda - Barugahara Evyline Isingoma (IWA Publishing, 2021)
There is scarcity of information about the safety of water in Banda slum of Kampala, Uganda and yet reports indicate outbreaks of infectious diseases such as typhoid fever and cholera. The aim of this study was to determine the risk of exposure to waterborne infections by Banda residents due to faecal contamination of water sources. Four hundred respondents were sampled and interviewed on the methods of water collection, treatment and storage. Water samples were collected with sterile glass bottles in duplicate from the dug well, protected spring and piped water system in December 2018 on two different consecutive days. They were transported to the laboratory for total and faecal coliform count analysis within 2 h using a lightproof-insulated box containing ice-packs. The mean Escherichia coli count for the dug well was 43 ± 18 c.f.u/mL. The protected spring had no detectable E. coli, but its total plate count level was 76 ± 1.4 c.f.u/mL. Only 46% of the respondents treated their drinking water using boiling and filtering methods. Poor sanitation and hygiene practices were observed. The total and faecal coliform counts of water sources were unsatisfactory making Banda residents highly at risk of infectious diseases, given the small number of residents that treated water. HIGHLIGHTS There are reports of waterborne diseases in Banda zone.; Lack of data on water sources and treatment methods in Banda slum.; Poor sanitary conditions in this slum.; Highly populated area with few social amenities.; Low educational levels of inhabitants.;